2021
DOI: 10.1097/jpa.0000000000000385
|View full text |Cite
|
Sign up to set email alerts
|

Physician Assistant Education Community Assumptions About an Entry-level Doctoral Degree

Abstract: Purpose This study described the assumptions that PA educators hold regarding the option and/or transition to a doctoral entry-level degree for PA graduates.Methods A cross-sectional electronic survey of all members of accredited PA programs was administered. The survey comprised 32 Likert-type statements that measured respondents' level of agreement ranging from strongly disagree to strongly agree and general demographic information. Mean scores are reported for each Likert statement and then compared with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 11 publications
3
18
0
Order By: Relevance
“…Overall, these two studies revealed that support for an entry-level doctorate was weak but that some respondents did support a doctorate as an option for PAs 5,6. These findings are consistent with previous studies that found that practicing PAs and PA students were not supportive of an entry-level doctorate for the PA profession 12,13.…”
Section: A Profession Dividedsupporting
confidence: 86%
See 1 more Smart Citation
“…Overall, these two studies revealed that support for an entry-level doctorate was weak but that some respondents did support a doctorate as an option for PAs 5,6. These findings are consistent with previous studies that found that practicing PAs and PA students were not supportive of an entry-level doctorate for the PA profession 12,13.…”
Section: A Profession Dividedsupporting
confidence: 86%
“…5 They also showed that a signifi cant portion of the survey respondents believed that a terminal doctoral degree was a barrier to increasing workforce diversity. 5 Overall, these two studies revealed that support for an entry-level doctorate was weak but that some respondents did support a doctorate as an option for PAs. 5,6 These fi ndings are consistent with previous studies that found that practicing PAs and PA students were not supportive of an entry-level doctorate for the PA profession.…”
Section: A Profession Dividedmentioning
confidence: 99%
“…Coplan et al (2009) conducted mixed-methods research to explore the opinions regarding an entry-level clinical doctorate among 152 PA program medical directors using a 16-item, non-validated survey [11]. Recently, a study conducted by Brown and colleagues (2020) addressed the potential impact of an entry-level doctorate on PAs and PA faculty and programs among 712 PA educators using a 32-item survey that has not been validated [16]. Although Muma et al (2011) included representative samples of physicians, PAs, and PA faculty to compare perceptions regarding the entry-level doctoral education, a non-validated instrument seemed to be used [14].…”
Section: 73mentioning
confidence: 99%
“…As the health care milieu continues to change, the quest for doctoral education for PAs has continued at various levels. As of 2022, about 11 institutions have established post-professional programs such as the Doctor of Medical Science [6,7,12,16,17]. However, the value, risks, and benefits are still subject to discussion, and the PA entry-level doctoral credential debate continues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation